Rising stars in the global race for skill? A comparative analysis of Brazil, India, and Malaysia. (21st May 2020) - Cerna, Lucie; Czaika, Mathias
Abstract: How do emerging economies compete for international skilled workers? To explore policies used by non-Western countries to attract or retain high-skilled workers in the context of the 'race for talent', this article analyses and compares governmental measures employed in three emerging economies: Brazil, India, and Malaysia. Based on insights from 17 expert interviews, we describe the practices and strategies of these three countries to reverse 'brain drain'—that is, the loss of human capital through migration. The article argues that the design and development of migration and skill recruitment policies are at different stages and of varying relevance to respective national actors. While Malaysia has become an active player and innovator on the international talent recruitment market, the other two countries still consider themselves as 'self-sufficient', relying on either their domestically produced human resources or, in the case of India, their skilled diaspora. The three countries are situated at different, mostly early stages of a 'migration policy transition', with rising demand for human capital, but still insufficient legal, administrative, and economic provisions to recruit and admit many skilled foreign workers. The 'global race for talent' is less of a race for the global South as it is in the global North.